2018
DOI: 10.5099/aj180100028
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Chrysophyllum Albidum Leaves, Fruits and Seeds

Abstract: Background: Chrysophyllum albidum is a medicinal plant that belongs to the Sapotaceae family. This study was carried out to determine the antimicrobial activities of the leaves, seeds and fruits of Chrysophyllum albidum.Materials and Methods: The fruits, leaves and seeds of Chrysophyllum albidum were extracted with distilled water, Seaman's Schnapps, Methanol and Petroleum ether using cold extraction. These extracts were tested on various organisms. Antimicrobial activities of the various extracts were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 10 publications
4
14
1
Order By: Relevance
“…This is higher when compared to the concentration of total phenolic content of C. albidumobtained from different organic solvent of extracts of the seed, fruit pulp and skin that yielded 6.72, 1.28 and 12.66 and that of the flavonoids were 9.42, 2.69 and 11.66 respectively expressed as mg/GAEq. 16 George et al 2 also detected flavonoids and steroids but not saponnins and tannins. The presence of flavonoids and phenolic in the extracts could be responsible for some of the beneficial effects attributed to the plant.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is higher when compared to the concentration of total phenolic content of C. albidumobtained from different organic solvent of extracts of the seed, fruit pulp and skin that yielded 6.72, 1.28 and 12.66 and that of the flavonoids were 9.42, 2.69 and 11.66 respectively expressed as mg/GAEq. 16 George et al 2 also detected flavonoids and steroids but not saponnins and tannins. The presence of flavonoids and phenolic in the extracts could be responsible for some of the beneficial effects attributed to the plant.…”
Section: Discussionmentioning
confidence: 97%
“…Such free radical scavenging potentials could prevent oxidative stress-related chronic diseases or disorders 22 . Morufuet al 2 reported positive result of the plants leaf which showed 69-88% with increasing concentration of extract. George et al 2 28 .…”
Section: Leafmentioning
confidence: 94%
See 1 more Smart Citation
“…Koffi et al (2009) claimed that alkaloids, flavonoids, phenols, sterols and triterpenes had been chemically examined in leaf of C. cainito, this has been applied to resist diabetes and rheumatoid arthritis. Nonetheless, a number of research reveal that leaf extracts of many Chysophyllum species have been used in the application of anticancer, antioxidant, antimicrobial and so on (Mallikarjun et al 2011;Meira et al 2014;Li et al 2015;Mao et al 2015;Hegde et al 2016;Ningsih et al 2016;Doan et al 2018;George et al 2018) In spite of a great number of benefits of the genus to the society, identification of Chrysophyllum has been found to be untenable. Most identification keys were constructed from their leaf and floral features (Chayamarit 2014) which are difficult for the users in identifying the plant because of the non-availability of the flowering stage and morphological similarities of a variety of species.…”
Section: Introductionmentioning
confidence: 99%
“…According to George et al (2018), the fleshy fruit pulp is suitable for jams and eaten especially as snacks by both young and old. Besides, C. albidum plant parts have been used in folk medicine.…”
Section: Introductionmentioning
confidence: 99%